New Trends in Basic and Clinical Research of Glaucoma - Bagetta, Giacinto (Elsevier, 2015)
Front Cover -- New Trends in Basic and Clinical Research of Glaucoma: A Neurodegenerative Disease of the Visual System, Part B -- Copyright -- Contributors -- Contents -- Preface: New Trends in Basic andClinical Research of Glaucoma:A Neurodegenerative Disease of theVisual System Part B -- Chapter 1: Molecular biomarkers in primary open-angle glaucoma: from noninvasive to invasive -- 1. Introduction: what is a biomarker? -- 2. Defining Biomarkers -- 2.1. Proteomics Technologies for Biomarker Identification -- 3. Noninvasive biomarkers in primary open-angle glaucoma -- 3.1. Tears Biomarkers -- 3.2. Urine Biomarkers -- 4. Minimally invasive biomarkers in primary open-angle glaucoma -- 4.1. Serum Biomarkers -- 4.1.1. Protein Biomarkers -- 4.1.1.1. Autoimmunity Markers -- 4.1.1.2. Inflammatory Markers -- 4.1.1.3. Neurodegenerative/Apoptotic Biomarkers -- 4.1.1.4. Oxidative Stress Markers -- 4.1.1.5. Biomarkers of Trabecular Meshwork Dysfunction -- 4.1.2. Genetic Biomarkers -- 5. Invasive biomarkers in primary open-angle glaucoma -- 5.1. Aqueous Humor Biomarkers -- 5.1.1. Trabecular Meshwork Damage Biomarkers -- 5.1.2. RGC Damage Biomarkers -- 5.1.3. Oxidative Stress Biomarkers -- 5.2. Vitreous Body Biomarkers -- 5.3. Cerebrospinal Fluid Biomarkers -- 6. Molecular Biomarkers in Clinical Practice: Is Translation Feasible? -- 7. Summary and Conclusions -- References -- Chapter 2: Cerebrospinal fluid pressure in the pathogenesis of glaucoma -- 1. Introduction -- 2. Anatomy and Dynamics of the Optic Nerve Head in Relationship to the Retrobulbar CSF Space -- 3. Intraocular Pressure -- 4. Relationship Between CSFP and IOP and Its Dynamics -- 5. CSFP, TLPD, and IOP: glaucomatous Optic Neuropathy -- 6. Limitations -- 7. Methods for Determining CSFP -- 8. CSFP and Retinal and Choroidal Vein Pressure -- References.
Description based upon print version of record
Keywords: Electronic books